MICROBIAL SAFETY OF STREET FOOD SAUCES : DETECTION OF ESCHERICHIA COLI AMONG VENDORS IN KLATEN REGENCY - Arini, Liss Dyah Dewi; Pramonodjati, Fredericus; Fitria, Azizah Zahra Nur (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Egg rolls are one type of food that requires additional ingredients in the form of sauce. Many egg sellers use bicycles or two-wheeled vehicles, with merchandise placed behind the bicycle or motorbike. However, the cleanliness of egg rolls is often ignored, one of the causes is exposure to dust and air that enters the food. This study aims to test for contamination of Eschericia coli bacteria and identify the presence of these bacteria in the sauce used in egg rolls. The method used in this study was a field survey with random and descriptive sampling techniques to determine the presence or absence of Eschericia coli in several types of sauces sold with egg rolls. Sampling was carried out by selecting 10 types of sauces from egg roll food sold around in Klaten Regency. Tests for Eschericia coli bacteria were carried out at the Biology Laboratory of Sebelas Maret University, Surakarta, and one sample as a negative control using the most probable number (MPN) method, Escherichia coli test and gram staining. The results of the Most Probabe Number test and confirmation test showed that there was Eschericia coli, while from the results of gram staining, the detected bacteria were included in the gram-negative category. The results of the biochemical test showed that the bacteria in the sample included the Enterobacter and Escherichia coli species. The tests carried out showed that all results did not meet the standards set in SNI 01-3546-2004, which regulates the maximum limit of the Total Plate Count (TPC) in tomato sauce is 2 x 10² colonies/g, while according to the Regulation of the Head of the Food and Drug Supervisory Agency of the Republic of Indonesia number HK. 00. 06. 1. 52. 401, the maximum limit of the Most Probable Number (MPN) Coliform in tomato sauce is 100 colonies/g.